KLASIFIKASI ALAT TRADISIONAL SAWAH PAYO KOMUNITAS ETNIK MELAYU JAMBI - Fadilah, Nurul; Maulina, Rini (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
Jambi Malay ethnic communities in the province of Jambi have livelihoods as farmers. In farming, they use the ways and tools of traditional. Farm tools of the Jambi Malay ethnic communities are the artifacts that need to be analyzed, scrutinized, and recorded as the corpus of the thinking and creativity of the community ancestor Jambi Malay. The aim of the research is classifying the traditional tools in farming system payo on Jambi Malay ethnic communities. The approach used in this study is the ethnographic and the methods used to obtain data is a research library, observation, and interviews. The research showed that Jambi Malay ethnic community uses traditional farming tools namely Parang Panjang, Kayu Pengait, Pangkur, Keruntung, Ambung, Tajak, Sabit, Kisaran, Nyiru, dan Tikar Rumbai. The Jambi Malay ethnic communities traditional tools classified into two major class i.e cutter (dynamic) and container (static) tools. Classification obtained is expected to motivate the holding of study, research, and comprehensive archiving of traditional agricultural tools of Jambi Malay ethnic communities as part of Indonesian culture artifacts.